Determination of water and oil flow composition using ultrasonic tomography techniques - Abdul Rahim, Ruzairi; Ng, Wei Yap; Rahiman, Mohd. Hafiz Fazalul; Chan, Kok San (Faculty of Electrical Engineering, 2007)

(untitled)
This paper presents an investigation into the application of an ultrasonic tomography system to determine the composition of water and oil flow. There are three modes of the ultrasonic tomography system, the transmission mode, reflection mode and the diffraction mode. In this research, the ultrasonic tomography system using the transmission mode was implemented. This method is also one of the non-invasive methods that do not disturb the internal flow of the pipeline. Hence, water and oil flow inside the pipe could be monitored by this system in an uninterrupted manner and the composition of the flow is determined based on the sum of all the sensor’s values. In this paper, the implementation method of the research is described and the acquired results are presented.